Drug Classification using Machine Learning Algorithms - Hengky fernando (Data Science Insights, 2025)
The right selection of drugs is a crucial factor in the treatment of various diseases to ensure the effectiveness of therapy and avoid risks that can worsen the patient's condition. This study aims to develop a machine learning-based prediction model to classify the appropriate type of drug based on patient characteristics. Several machine learning algorithms are tested to determine the most optimal model. The results of the analysis show that the Random Forest algorithm provides the best performance with the highest level of accuracy in predicting the right type of drug. Thus, the Random Forest-based model is recommended to be implemented as a decision support tool in the selection of drug therapies that is more accurate and efficient.